KONTRIBUSI PENGALAMAN PRAKERIN TERHADAP MINAT BERWIRAUSAHA SISWA SMK PROGRAM STUDI KEAHLIAN TEKNIK BANGUNAN - Hasbi Hasbi (Jurnal Pendidikan Teknik Sipil, 2019)
ABSTRACTEntrepreneurship education in order to foster interest in entrepreneurship for vocational high school students is an important aspect in accustoming graduates who are able to create employment. Sample of this research was entire Vocational High School students of Architecture Engineering Courses in Malang who has carried out on-the job training as many as 108 students. Based on the analysis by looking at propensity scores showed that: students' entrepreneurship categorized as high contribution. From 108 respondents, 11 students or 10.26% categorized as very high contribution, 47 students or 43.52%, categorized as high contribution, 28 students or 25.92%, categorized as adequate contribution, and 22 students or 20.38% categorized as low contribution. Based on these results, it can be concluded that interest in entrepreneurship is influenced by experience of on-the-job-training which experience provides knowledge and experience, so as to accustom a student's interest in entrepreneurship. Keywords: entrepreneurship interest, On-the-Job Training experience, vocational high school ABSTRAKPenanaman  kewirausahaan  dalam  menumbuhkan minat berwirausaha bagi siswa SMK merupakan aspek penting dalam menghasilkan  lulusan  yang  mampu  menciptakan lapangan  kerja  (berwirausaha). Sampel dalam penelitian ini adalah seluruh siswa SMK Paket Keahlian Teknik Gambar Bangunan di Malang yang telah melaksanakan Prakerin sebanyak 108 orang siswa.  Berdasarkan hasil analisis dengan melihat kecenderungan skor yang diperoleh, minat berwirausaha siswa termasuk dalam kategori tinggi. Dari 108 orang responden, yang termasuk pada kategori sangat tinggi sebanyak 11 orang atau sekitar 10,26%;, kategori tinggi sebanyak 47 orang atau sekitar 43,52%, kategori cukup sebanyak 28 orang atau sekitar 25,92%, dan kategori kurang sebanyak 22 orang atau sekitar 20,38%. Berdasarkan hasil penelitian tersebut, maka dapat disimpulkan bahwa Minat berwirausaha  dipengaruhi  oleh  pengalaman prakerin dimana pengalaman memberikan pengetahuan dan pengalaman dalam bekerja, sehingga dapat membentuk minat siswa dalam berwirausaha.  Kata kunci: minat berwirausaha, pengalaman prakerin, sekolah menengah kejuruan